Parathyroid Hormone Derivative with Reduced Osteoclastic Activity Promoted Bone Regeneration via Synergistic Bone Remodeling and Angiogenesis. Issue 6 (21st January 2020) - Huang, Jinghuan; Lin, Dan; Wei, Zhanying; Li, Qi; Zheng, Jin; Zheng, Qixin; Cai, Lin; Li, Xiaolin; Yuan, Yuan; Li, Jingfeng
Abstract: Osteogenesis, osteoclastogenesis, and angiogenesis are the most important processes in bone repair. Parathyroid hormone (PTH) has pro‐osteogenic, pro‐osteoclastogenic, and proangiogenic effects and may be a candidate for use in bone defect repair. However, the local application of PTH to bone defects is counterproductive due to its excessive osteoclastic and bone resorptive effects. In this study, a PTH derivative, PTHrP‐2, is developed that can be applied to local bone defects. First, a modified peptide with a calcium‐binding repeat glutamine tail undergoes controlled local release from a ceramic material and is shown to be a better fit for the repair process than the unmodified peptide. Second, the modified peptide is shown to have strong pro‐osteogenic activity due to mineralization and its facilitation of serine (Ser) phosphorylation. Third, the modified peptide is shown to maintain the pro‐osteoclastogenic and proangiogenic properties of the unmodified peptide, but its pro‐osteoclastogenic activity is reduced compared to that of the unmodified peptide. The reduced pro‐osteoclastogenic and increased pro‐osteogenic properties of the modified peptide reverse the imbalance between osteoblasts and osteoclasts with local PTH application and shift bone resorption to bone regeneration. Abstract : Parathyroid hormone (PTH) is a potential bone repair agent, but its application is limited due to overwhelming osteoclastic activity. PTHrP‐2 is created by structural modification and shows controlled release characteristics, enhanced pro‐osteogenic and proangiogenic properties. Surprisingly, the modification of PTH reduces its pro‐osteoclastic properties. Therefore, PTHrP‐2 can be used in local bone repair and extends the application scope of PTH.